Synthesis and applications of Fe3O4- diisopropylaminoacetamide as a versatile and reusable magnetic nanoparticle supported N,N-diisopropylethylamine equivalent - Parintip Rattanaburi (2018)
A magnetic nanoparticle supported N,N-diisopropylaminoacetamide (Fe3O4-DIPA) was developed for application as a magnetic recoverable, and reusable N,N-diisopropylethylamine equivalent. The Fe3O4nanoparticles were coated with a silica layer using the sol-gel method, followed by surface modification with 3- aminopropyltriethoxysilane. Subsequent acylation with chloroacetyl chloride and chlorine displacement with diisopropylamine afforded Fe3O4-DIPA in 90% yield with a loading of 0.96 mmol/g. The applicability of Fe3O4-DIPA was demonstrated in the synthesis of amine derivatives cv sulfonation, acylation, and N-alkylation reactions. The desired products were obtained in excellent yields and purities after scavenging the residual starting amines by treatment with silica-supported dichlorotriazine. Fe3O4-DIPA was readily recovered by separation using a magnet and could be reused several times without significant loss of reactivity. © 2012 Elsevier Ltd. All rights reserved.